1991
DOI: 10.1152/ajplung.1991.261.4.l349
|View full text |Cite
|
Sign up to set email alerts
|

Genetic element from human surfactant protein SP-C gene confers bronchiolar-alveolar cell specificity in transgenic mice

Abstract: Transgenic mice bearing chimeric genes consisting of 5'-sequences derived from the human surfactant protein C (SP-C) gene and the bacterial chloramphenicol acetyltransferase (CAT) gene were generated. Analysis of CAT activity was utilized to demonstrate tissue-specific and developmental expression of chimeric genes containing 3.7 kb of sequences from the human SP-C gene. Lung-specific expression of the 3.7 SP-C-CAT transgene was observed in eight distinct transgenic mouse lines. Expression of the 3.7 SP-C-CAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
76
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 14 publications
10
76
1
Order By: Relevance
“…The pattern of expression is most prominent in the lung peripheral epithelium, consistent with previous published studies of transgenic mice bearing the SP-C promoter constructs (Glasser et al, 1991;Wert et al, 1993;Zhou et al, 1997;Zeng et al, 2001). …”
Section: Expression Of the Notch3 And Sp-c-n3ic Transgenesupporting
confidence: 90%
See 2 more Smart Citations
“…The pattern of expression is most prominent in the lung peripheral epithelium, consistent with previous published studies of transgenic mice bearing the SP-C promoter constructs (Glasser et al, 1991;Wert et al, 1993;Zhou et al, 1997;Zeng et al, 2001). …”
Section: Expression Of the Notch3 And Sp-c-n3ic Transgenesupporting
confidence: 90%
“…In these transgenic embryos, the pancreatic epithelium was poorly branched and reduced in size. The variability in branching morphogenesis seen in the SP-C-N3IC transgenics may be a result of the transcription of SP-C gene as early as E10.5, when branching morphogenesis is still occurring, and the differences in the expression among transgenics (Glasser et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenes were each driven by the human surfactant C (SP-C) promoter ( Fig. 2A), which conferred expression in alveolar type II and bronchioalveolar cells (23). Two independent WT cyclin E and two independent degradation-resistant cyclin E founder mice were identified by Southern blot analyses (data not shown).…”
Section: Results Sirna Targeting Of Cyclin Ementioning
confidence: 99%
“…These animals exhibited either a limited expression of GFP only in some AT2 cells (27), or a broad expression of GFP in both bronchiolar and AT2 cells (29). Previous studies also demonstrated the importance of species-specific promoter use for proper AT2 cell expression (30,31). Further detailed analysis of the murine SPC gene promoter revealed the particular sequences needed for (Received in original form November 22, 2011 and in final form October 19, 2012) AT2 cell-specific expression (32).…”
mentioning
confidence: 92%